2019
DOI: 10.1136/bmjopen-2019-031242
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the measurement properties of performance-based functional tests in patients with neck disorders

Abstract: ObjectivesThe purpose of this systematic review is to identify and synthesise studies evaluating performance-based functional outcome measures designed to evaluate the functional abilities of patients with neck pain.DesignSystematic review.Data sourcesA literature search using PubMed, Scopus, CINAHL, EMBASE, COCHRANE, Google Scholar and a citation mapping strategy was conducted until July 2019.Eligibility criteriaMore than half of the study’s patient population had neck pain or a musculoskeletal neck disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Instead, we have relied on more qualitative syntheses of previously reported data to identify consistencies and differences in findings. We also acknowledge that the quality appraisal tool (QACMMRE), while it has been used in several prior systematic reviews, [94][95][96] is less commonly used than COSMIN tools. This was an intentional decision, as our initial attempts at applying the COSMIN checklist to studies evaluating the single-item NPRS resulted in the majority of sections being deemed not applicable and precluded our ability to discriminate between levels of study quality.…”
Section: Limitationsmentioning
confidence: 99%
“…Instead, we have relied on more qualitative syntheses of previously reported data to identify consistencies and differences in findings. We also acknowledge that the quality appraisal tool (QACMMRE), while it has been used in several prior systematic reviews, [94][95][96] is less commonly used than COSMIN tools. This was an intentional decision, as our initial attempts at applying the COSMIN checklist to studies evaluating the single-item NPRS resulted in the majority of sections being deemed not applicable and precluded our ability to discriminate between levels of study quality.…”
Section: Limitationsmentioning
confidence: 99%
“…These can lead to functional disability [ 2 , 25 , 26 ], participation restrictions [ 27 ], reduced work capacity [ 28 – 30 ], and lower quality of life [ 31 , 32 ]. There are a variety of impairment and disability measures that have been designed to assess these different constructs [ 23 , 33 38 ]. A survey of international practice patterns of clinicians with respect to assessing the outcomes for patients with neck pain indicated that the Numeric Pain Rating Scale (NPR) (a single item on pain [ 37 ]), the Neck Disability Index (NDI), and the Disabilities of the Arm, Shoulder and Hand (DASH) (developed for upper extremity [ 39 ]) are the patient-reported outcome measures (PROMs) most commonly used by clinicians [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patient-reported outcome measures (PROMs) are often administered to assess any health-related changes that may have occurred as a consequence of health-management interventions [ 7 , 8 ]. Many properties are important [ 9 13 ] during an instrument development such as reliability and validity but a key property is considered to be content validity [ 14 ]. Content validity can be defined as the degree of which the instrument or the questionnaire is an adequate reflection of the construct being measured [ 15 ].…”
Section: Introductionmentioning
confidence: 99%